Sistem Pendeteksi Jenis Buah Mangga Menggunakan Metode Template Matching - Agung Bachtiar Sukmaarta; Dahnial Syauqy; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Template Matching Algorithm is a simple method used to recognize patterns in an image. Template Matching Methods are often used to identify letters, numbers, fingerprint and other image matching images. In this research is made a system to detect type of mango fruit. There are 3 types of mangoes that can be detected, namely Manalagi, Arumanis, and Golek. The method used in this application is Template Matching, which is a statistical technique used to find two variables / matrices or more that are quantitative. This algorithm matches each pixel in a digital image matrix of mango from the image that becomes the template reference. The results of the experiments show that the classification of the type of mango fruit with Template Matching method can detect images of tested mangoes. The success rate of mango fruit detection is 70.83% of the test data of 24 images. Performance of Mango Type Detection System with Template Matching Method has average value of average speed of 4.075 seconds from 24 times testing.